Mixed-halide perovskites solar cells through PbICl and PbCl2 precursor films by sequential chemical vapor deposition. (February 2021) - Ngqoloda, Siphelo; Arendse, Christopher J.; Guha, Suchismita; Muller, Theophillus F.; Klue, Stephen C.; Magubane, Siphesihle S.; Oliphant, Clive J.
Highlights: Lead halides deposition and conversion to perovskites by chemical vapor deposition method. Formation of stable lead chloride iodide thin film. Chlorine substitution by iodine during perovskite conversion step. Perovskite thin films with micron size grains. Improved perovskite solar cell device performance by chlorine doping. Abstract: Mixed halide perovskites with chlorine (Cl) content have received significant interest due to better charge transport properties and longer diffusion length compared to pure iodine-based perovskites. The superior properties of Cl-doped perovskites improve solar cell device performance, although the quantification of Cl composition in the perovskite films remain difficult to achieve. Hence, it is difficult to correlate the Cl-quantity with the improved device performance. In this work, we deposited Cl-doped perovskite films through a facile three- and two-step sequential chemical vapor deposition (CVD) where lead halide films were deposited in the first steps of the process and subsequently converted to perovskites. No Cl substitution by iodine was observed during a sequential deposition of lead chloride and lead iodide films which reacted to form a lead chloride iodide phase (PbICl). The substitution of Cl by iodine ions only occurred during the conversion to perovskite phase. Large perovskite grains (greater than 2 µm) were realized when converting a PbI2 film to perovskite compared to chlorine containing lead halide films, contradicting literature. However, Cl doped perovskite solar cells showed improved device efficiencies as high as 10.87% compared to an un-doped perovskite solar cell (8.76%).